2020 International Conference on Mathematics and Computers in Science and Engineering (MACISE) 2020
DOI: 10.1109/macise49704.2020.00025
|View full text |Cite
|
Sign up to set email alerts
|

Control properties of multiagent dynamical systems modelling brain neural networks

Abstract: The control of linear dynamical systems is a strategy that the brain uses to control its own intrinsic dynamics. The brain structure can be modelled as a networked system that is expressly interesting system to control because of the role of the underlying architecture, which predisposes some components to particular control motions. The concept of brain cognitive control defined by neuroscientists is related to the mathematical concept of control defined by physicists, mathematicians, and engineers, where the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…Controllability is one of the most important properties of dynamical systems, and that is why a great portion of the literature refers to this concept ( [6,8,9], among others).…”
Section: Controllability and Exact Controllabilitymentioning
confidence: 99%
See 2 more Smart Citations
“…Controllability is one of the most important properties of dynamical systems, and that is why a great portion of the literature refers to this concept ( [6,8,9], among others).…”
Section: Controllability and Exact Controllabilitymentioning
confidence: 99%
“…García-Planas in [6] showed that a noise-free multisystem of linear discrete-time and time-invariant model…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…García-Planas in [5] showed that a noise-free multisystem of linear discrete-time and time-invariant model…”
Section: Networkmentioning
confidence: 99%